Examining The Educational Learning Environment Through the Lens of Students (People's Journal of Management, 2024)
Ensuring high-quality educational experiences for students requires understanding their perspectives of the learning environment. However, studies examining gender differences in perceptions are limited. This study employed a cross-sectional survey design using the validated DREEM instrument. A sample of 131 students rated domains like learning, teaching, achievement and atmosphere. Students reported moderately positive overall views. Mean ratings ranged from 3.46-3.81 on a 5-point scale, indicating aspects were generally favorable while some opportunities for improvement also emerged. However, females expressed slightly more favorable opinions than males across domains. The findings provide valuable insights into People's Campus' learning environment. Addressing gaps through evidence-based initiatives focused on gender equity can help optimize outcomes for all students. Regular assessments maintaining responsiveness to evolving student needs are recommended. This research contributes novel local data evaluating student experiences and potential disparities through a gender lens.